Prospects for the development of the penal correction system - Shnarbayev, B.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The article discusses the need for an integrated approach to the development of the country's penal system. The importance of taking into account legal, technical, environmental, economic, organizational, social, psychological, political, demographic aspects that are important for resolving the issue is substantiated. The necessity of defining approaches to the issues of resocialization, the presence of controversial opinions regarding the terminology «correction» and «resocialization» is considered. Attention is focused on compensation for the harm caused to the victims of the crime, which amounts to hundreds of billions of tenge, while the compensation does not even amount to a tenth. According to unofficial data, compensation to victims of material damage by persons serving imprisonment is as follows: in 2019 the damage amounted to 597 billion tenge, compensation 1.4 billion tenge (0.23 %), in 2020, respectively, 451.2 and 1.7 billion tenge (0.37 %). The emphasis placed on the need for a thorough study of this issue, which should be among the first in the study of the problems and prospects of the penal system. The conclusion is summarized that the penitentiary system should be a comprehensive education, in which the main issues of legal support, pedagogy and psychology, social work, organization of the labor process should represent a common whole, without division into parts.